Validation of END-of-life ScorING-system to identify the dying patient: a prospective analysis - Gianluca Villa; Timothy Amass; Rosa Giua; Iacopo Lanini; Cosimo Chelazzi; Lorenzo Tofani; Rory McFadden; A. Raffaele De Gaudio; Sean OMahony; Mitchell M. Levy; Stefano Romagnoli (BMC Anesthesiology, 2020)
Abstract Background The “END-of-Life ScorING-System” (ENDING-S) was previously developed to identify patients at high-risk of dying in the ICU and to facilitate a practical integration between palliative and intensive care. The aim of this study is to prospectively validate ENDING-S in a cohort of long-term critical care patients. Materials and methods Adult long-term ICU patients (with a length-of-stay> 4 days) were considered for this prospective multicenter observational study. ENDING-S and SOFA score were calculated daily and evaluated against the patient’s ICU outcome. The predictive properties were evaluated through a receiver operating characteristic (ROC) analysis. Results Two hundred twenty patients were enrolled for this study. Among these, 21.46% died during the ICU stay. ENDING-S correctly predicted the ICU outcome in 71.4% of patients. Sensitivity, specificity, positive and negative predictive values associated with the previously identified ENDING-S cut-off of 11.5 were 68.1, 72.3, 60 and 89.3%, respectively. ROC-AUC for outcome prediction was 0.79 for ENDING-S and 0.88 for SOFA in this cohort. Conclusions ENDING-S, while not as accurately as in the pilot study, demonstrated acceptable discrimination properties in identifying long-term ICU patients at very high-risk of dying. ENDING-S may be a useful tool aimed at facilitating a practical integration between palliative, end-of-life and intensive care. Trial registration Clinicaltrials.gov Identifier: NCT02875912 ; First registration August 4, 2016.